Talent Identification in an English Premiership Rugby Union Academy: Multidisciplinary Characteristics of Selected and Non-selected Male Under-15 Players - Dimundo, Francesco; Cole, Matthew; Blagrove, Richard C.; McAuley, Alexander B. T.; Till, Kevin; Kelly, Adam L. (Frontiers in Sports and Active Living, 2021)
Entry into an academy can be a defining moment for a promising young player. The aim of this study was to explore the multidimensional characteristics that differentiated selected and non-selected male under-15 rugby union players at an English Premiership academy. Seventy-four players (mean age 14.6±0.3 years: selected n=29; non-selected n=45) were measured across nine characteristics from four overarching factors: (a) anthropometric (n=2), (b) physiological (n=5), (c) cognitive (n=1), and (d) birth quartile. An ANOVA compared differences between groups (selected vs. non-selected), whilst a Welch’s t-test and Cohen’s d were used for further comparisons. A multivariate logistic regression was also used to predict selection. Results showed significant differences between selected and non-selected players for anthropometric (P=0.021) and physiological factors (P<0.001). Moreover, relatively older players were overrepresented with 65% born in the first half of the year, whereas no significant differences were apparent for the cognitive test. More specifically, selected players possessed greater body mass (P=0.022, d=0.5) and handgrip strength (P=0.020, d=0.5) compared to non-selected players, whilst multivariate analysis showed the 20 m sprint explained 25.4% of the variance (P=0.001). Overall, it appears selection into an English Premiership rugby union academy may be due to enhanced physical attributes rather than cognitive abilities.